The fetters of rhyme : liberty and poetic form in early modern England - Rush, Rebecca M., 1987- (Princeton University Press, 2021)
"Long before the English fought a civil war over the meaning of liberty, poets were debating the benefits of constraint and the risks of bond-breaking. Early modern poets imagined rhyme as a band or fetter, and compared rhyme to the bonds that tie individuals to political, social, and religious communities. Because they believed that verse forms reflected cosmic and political patterns, early modern authors maintained that formal choices were never ideologically neutral. The charged nature of early modern forms is particularly visible in the dynamic history of the couplet: In the 1590s, poets like John Donne took up the Chaucerian couplet to signal their sexual and political radicalism, but by the middle of the seventeenth century Royalist poets had co-opted the couplet as a tool for reinforcing affective ties to king and country"--